1
$\begingroup$

I have been asked to assume a power series solution of the form

$$y(x)= \sum_{n=0}^\infty a_n x^n $$

is a solution of the homogeneous linear ODE

$$y^\prime-(1+2x)y=0, $$

Obtain a recursion for the coefficients and use these recursions to determine the series representation of the solution.

I know the solution to the ODE is $y(x)=e^{x(x+1)}$ from a previous problem.

So far I have managed to simply the equation down to

$$ a_1-a_0+\sum_{m=1}^\infty [a_{m+1}(m+1)-a_m-2a_{m-1}]x^m = 0$$

I'm not sure where to go from here to complete the problem.

$\endgroup$
1
$\begingroup$

The function you have written on the left can only be equal to zero if the coefficient of $x^m$ is equal to zero for each $m$ (otherwise, the $m$th derivative at zero will not be zero, right?). Therefore you have the recurrence relation $$ a_{m+1} = \frac{a_m+2a_{m-1}}{m+1} $$ for every $m \geq 1$. The constant term gives you $a_0=a_1$ in the same way. It's not obvious what the solution to this recurrence is, so stick in the first few and let's see what happens: set $a_0=A$, and we find $$ a_0=A,\quad a_1 = A, \quad a_2 = \frac{a_1+2a_0}{1+1} = \frac{3}{2}A, \quad a_3 = \frac{3/2+2}{3}A = \frac{7}{6}A $$

Unfortunately there is, as far as I know, no closed form for this. (Knowing the solution, you can find a representation using the Cauchy product of the series for $e^{x^2}$ and $e^x$, but that's a lot harder to produce from the recurrence.)

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.